A 2D diffeomorphic image registration model with inequality constraint. (15th February 2023) - Han, Huan; Jin, Qi; Zhang, Yimin
Abstract: In this paper, we relax the equality constraints of the diffeomorphic image registration in Han and Wang (2020) [9] to equality and inequality constraints. Then, the mesh folding is eliminated. Moreover, a numerical algorithm for the proposed model is presented. Numerical tests are also performed to show that the proposed algorithm is competitive compared with some published image registration models.